Profile of Trace Elements in Selected Medicinal Plants Used for the Treatment of Diabetes in Eritrea - Mussie Sium; Patrick Kareru; Joseph Keriko; Berhane Girmay; Ghebrehiwet Medhanie; Semere Debretsion (The Scientific World Journal)
This study was designed to investigate the profile of certain trace elements having therapeutic properties related to diabetes mellitus. The investigated plants were Aloe camperi, Meriandra dianthera, Lepidium sativum, Brassica nigra, and Nigella sativa. These plants are traditionally used in the management of diabetes in Eritrea. The elemental analysis was conducted using inductively coupled plasma optical emission spectrometry (ICP-OES) and flame atomic absorption spectroscopy (FAAS) techniques. The accuracy of the methods was verified using in-house reference materials (CRMs) and no significant differences were observed between the measured and certified values. The analysis displayed variable concentrations of the different trace elements including Zn, Cr, V, Mn, and Se in the plants. Moreover, the levels of major elements, such as Mg, Ca, K, Na, and Ba, and heavy metals, such as Fe, Cu, Ni, Co, As, and Pb, were determined and found to be in the permissible limit defined by WHO. Among the plants, Meriandra dianthera showed the highest levels of Mn, Cr, V, and other elements and the values were significantly different (P<0.05).